Analisis Hambatan Guru IPS Dalam Pembelajaran Daring Pada Masa Pandemi Covid-19 (Studi Kasus Pada Sekolah Menengah Pertama/Setara Di Kabupaten Tulungagung) - yunifa anisauzahro; Nailariza Umami (LPPM Universitas PGRI Adi Buana Surabaya, 2022)
The main problem in this study is that researchers want to reveal how the social studies teacher's barriers in online learning during the covid-19 pandemic. The purpose of this research is to find out the obstacles experienced by social studies teachers in the implementation of online learning and practical solutions in implementing online learning. This type of research is descriptive qualitative. Data collection techniques in this study were observation, interviews and documentation. The results of this study are the first, namely an inadequate internet network during online learning. The second is the boredom and lazy attitude of students. Saturated and lazy are psychological conditions of students. Third, namely the ability of students to use learning applications. Fourth, ownership of internet data quota. Limitations in purchasing quotas. The solution to the problem of online learning is by implementing limited face to-face activities, which can be used to collect assignments for students who do not have a stable internet network. As a solution to the boredom of the lazy attitude of students. Social Studies teachers always provide the latest social studies material references, which are in accordance with the current phenomena. Social Studies teachers provide guidance and direction to students who have not mastered how to operate the application. The solution to the barriers to quota ownership is to take advantage of quota assistance from the government.